Development of Comprehensive Evaluation Model of Free Trade Port Investment under Macroeconomic Support. (11th October 2022) - Zhang, Haitian; Benxue, Wang
Abstract : The financial benchmark rate of return is gradually declining, and the free trade port policy is not enough to improve the investment financial benchmark rate of return. Therefore, a comprehensive evaluation model for free trade port investment under the support of macroeconomics is proposed. A theoretical model of free trade port investment price fluctuations and monetary policy response is constructed under the support of macroeconomics, and the model is used to observe the impact of changes in free trade port investment prices on the economic effects of monetary control policies; thus, free trade port investment price fluctuations are constructed and as a result, a theoretical model of investment price fluctuations and interest rate policy responses in the free trade port is constructed to observe the impact of changes in investment prices in the free trade port on the economic effects of interest rate regulation policies; a theoretical model of investment and fiscal and taxation policy responses in the free trade port is constructed to observe the impact of changes in investment in the free trade port on the economic effects of fiscal and taxation policies. Explore the path of optimizing the comprehensive investment evaluation environment in the pilot free trade zone, and realize the development of a comprehensive evaluation model for investment in the free trade port. The experimental results show that the model can realize the comprehensive evaluation of free trade port investment under the support of the macroeconomy and has a good evaluation effect.